2014
DOI: 10.1016/s1665-6423(14)70090-2
|View full text |Cite
|
Sign up to set email alerts
|

A Parameter Free BBN Discriminant Function for Optimum Model Complexity versus Goodness of Data Fitting

Abstract: Bayesian Belief Network (BBN) is an appealing classification model for learning causal and noncausal dependencies among a set of query variables. It is a challenging task to learning BBN structure from observational data because of pool of large number of candidate network structures. In this study, we have addressed the issue of goodness of data fitting versus model complexity. While doing so, we have proposed discriminant function which is non-parametric, free of implicit assumptions but delivering better cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is already highlighted that feature selection can play an important role in evaluation of a classifier's performance. It is reported that little attention has been applied in evaluating the performance of BBN prior to its induction [11]. We can express our confidence that FSS is a key to estimation of performance of BBN prior to its induction phase in a real system.…”
Section: Bayesian Belief Network Scoring Functionmentioning
confidence: 68%
See 1 more Smart Citation
“…It is already highlighted that feature selection can play an important role in evaluation of a classifier's performance. It is reported that little attention has been applied in evaluating the performance of BBN prior to its induction [11]. We can express our confidence that FSS is a key to estimation of performance of BBN prior to its induction phase in a real system.…”
Section: Bayesian Belief Network Scoring Functionmentioning
confidence: 68%
“…They classified the techniques according to suitability, variety, usage and potential to sequence analysis and micorarray analysis. Although the pool of FSS techniques is becoming larger and larger [4,[10][11]; nevertheless specific exhaustive review leading to a wealth of comparative report for Bayesian belief network's various scoring function is not addressed so far. We in this study have incremented useful information in these survey reports; moreover our analysis is more precise in tweaking BBN in particular.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This method defines the discriminant function using log likelihood. The log likelihood refers to a method of extracting parameters from a set of data while the discriminant function refers to a function that determines the category of a parameter [ 39 ]. The classification error function is defined by applying , which is the log likelihood of the feature vector , to the model parameter to Equation (12): …”
Section: Resultsmentioning
confidence: 99%